Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store
seo-qna
SearchIcon
banner

If \[p\left( x \right) = {x^2} - 2\sqrt {2x} + 1\]then \[p\left( {2\sqrt 2 } \right)\] is equal to

Answer
VerifiedVerified
628.5k+ views
We have
\[\begin{gathered}
  p\left( x \right) = {x^2} - 2\sqrt {2x} + 1 \\
  p\left( {2\sqrt 2 } \right){\left( {2\sqrt 2 } \right)^2} - 2\sqrt 2 \left( {2\sqrt 2 } \right) + 1 \\
   = 8 - 8 + 1 \\
   = 1 \\
\end{gathered} \]
Hence, (b) is the correct answer.